Unintended Impacts of Public Investments on Private Decisions: The Depletion of Forested Wetlands - Stavins, Robert N.; Jaffe, Adam B. (American Economic Review, 1990)
By affecting relative economic returns, public infrastructure investments can induce major changes in private land use. We find that 30 percent of forested wetland depletion in the Mississippi Valley has resulted from private decisions induced by federal flood-control projects, despite explicit federal policy to preserve wetlands. Our model aggregates individual land-use decisions using a parametric distribution of unobserved land quality; dynamic simulations are used to quantify the impacts on wetlands of federal projects and other factors.